Trade Unions and the Welfare of Rural-Urban Migrant Workers in China. (August 2022) - Booth, Alison; Freeman, Richard; Meng, Xin; Zhang, Jilu
Using a panel survey, the authors investigate how the welfare of rural-urban migrant workers in China is affected by trade union presence at the workplace. Controlling for individual fixed effects, they find the following. Relative to workers from workplaces without union presence or with inactive unions, both union-covered non-members and union members in workplaces with active unions earn higher monthly income, are more likely to have a written contract, be covered by social insurances, receive fringe benefits, express work-related grievances through official channels, feel more satisfied with their lives, and are less likely to have mental health problems.